Occupational Therapy Assistant Students ' Perspectives About the Development of Clinical Reasoning - Jeanne M. Coviello; Marie Christine Potvin; LaRonda Lockhart-Keene (Scholarworks @ WMU, 2019)
A mandatory component of the training of occupational therapy assistant (OTA) students is the development of their clinical reasoning skills. As the demand for OTAs continues to increase in response to the growing need for occupational therapy services, the number of academic programs to prepare these future therapists has expanded. Unfortunately, there is no empirical literature addressing the preparation of OTA students, specifically the development of their clinical reasoning skills. Artifact analysis, focus groups, and questionnaires were used to explore OTA students' perceptions of what Level II fieldwork learning experiences facilitated the development of their clinical reasoning skills. The results suggest OTA students develop clinical reasoning skills during Level II fieldwork by engaging in a variety of learning experiences with support from fieldwork educators who are welcoming and approachable. Learning experiences that students perceived as most helpful to the development of clinical reasoning included hands-on learning, opportunities to witness best practice, receipt of clear expectations and regular feedback, gradual responsibility for caseload management, and opportunities for collaboration. This study adds to the profession's body of knowledge and has implications for OTA educators, fieldwork educators, OTA students, and future consumers of occupational therapy services.